The Level of Instructional Leadership Practices Among Principals of National Religious Secondary School in Malaysia (International Journal of Scientific Research and Management (IJSRM), 2019)
It is stated that Instructional leaders are responsible for making sure that positive attitude towards change is organised and created among members of the school. The study aimed to identify the level of Instructional Leadership practices among principals of the National Religious Secondary School in Malaysia. A total of 365 respondents from 57 National Religious Secondary Schools were selected by systematic random sampling method to answer the questionaires. Data is analyzed by using descriptive statistics identifying the mean, standard deviation and percentage to recognise the level. The result showed that the level of Instructional Leadership practices is significantly high (mean=3.85, s.d.=0.41). In conclusion, the study found that the level of Instructional Leadership Practices is high among the principals of the schools. The research implied that Instructional Leadership plays an important role and should be adopted by the principals and teachers of National Religious Secondary School to increase School Achievement. Keywords: Instructional Leadership, Principals, National Religious Secondary School, School Achievement